Fundamentals of Entrepreneurship (ent300) Business Plan: Fish and Cheap Business Plan / Nurul Nazirah Hanis Binti Mohd Jasni - Mohd Jasni, Nurul Nazirah Hanis; Awang Hasbi, Dayang Affifah Ilyana; Misli, Nashrul Akmal; Mohd Rasdi, Mohd Fareez; Zahir, Muhd Amir Akmal (2017)
Fish and cheap food truck is a business that supply fast food with a fish-themed menu that includes fish and chips, fish burger and fish taco. As seen on our business name, we aim to sell our product at a cheap price without sacrificing our profit. Our business is located at Lot 649, Piasau Jaya Lorong 1 A, Miri, 98000, Sarawak. We choose Miri as a place for us to enter our food truck business because in Miri there are existing food truck and we believe entering an existing market is much easier. Furthermore, local people in Miri shows a lot of interest in buying food from a food truck. Our business consist of business partners that shares approximate amount of capital in order to start our business. Our partners consist of five people and each have their own respective position that includes General Manager, Administrative Manager, Marketing Manager, Operational Manager and Financial Manager. We also found out that our government is providing a grant of RM 10,000 for food truck businesses. Therefore, it is a great opportunity for us to enter this venture. Our food truck menu consist of food that are well known from Britain, American and Mexican culture and as for that we want to promote these food here in Miri. We aim to deliver a unique and delicious food that are close to the authentic taste foreign food. We value importance of quality in our service as we believe that it is the key to have customers that we be loyal to us in years to come.